2014
DOI: 10.2334/josnusd.56.135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of salivary and serum lipid peroxidation, and glutathione in oral leukoplakia and oral squamous cell carcinoma

Abstract: Lipid peroxidation induced by reactiveoxygen species (ROS) is involved in the pathogenesis of malignancy. Overall, lipid peroxidation levels are indicated by malondialdehyde (MDA), which is the most frequently used biomarker to detect oxidative changes. Antioxidant defense systems such as glutathione (GSH) limit cell injury induced by ROS. Therefore, MDA and GSH can be used to monitor oxidative stress (OS). Hence, this study aimed to evaluate and compare both salivary and serum levels of MDA and GSH in oral le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 38 publications
4
40
0
3
Order By: Relevance
“…Metgud et al showed a significant increase of MDA and reduction of GSH progressively from healthy controls to pre-cancerous and to patients with OSCC, in line with a state of oxidative stress related to OSCC. This finding supports the hypothesis that ROS metabolism is markedly altered in cancer cells, leading to enhanced production of ROS compared to non-neoplastic cells, and the suppression of the antioxidant system that mediate body's defense mechanisms (90). For OSCC, as for most other cancer types, the prognosis depends largely on lifestyle factors, medical comorbidity, grading and tumor staging.…”
Section: Oral Pemphigus Vulgaris (Opv)supporting
confidence: 78%
See 1 more Smart Citation
“…Metgud et al showed a significant increase of MDA and reduction of GSH progressively from healthy controls to pre-cancerous and to patients with OSCC, in line with a state of oxidative stress related to OSCC. This finding supports the hypothesis that ROS metabolism is markedly altered in cancer cells, leading to enhanced production of ROS compared to non-neoplastic cells, and the suppression of the antioxidant system that mediate body's defense mechanisms (90). For OSCC, as for most other cancer types, the prognosis depends largely on lifestyle factors, medical comorbidity, grading and tumor staging.…”
Section: Oral Pemphigus Vulgaris (Opv)supporting
confidence: 78%
“…Another interesting study, carried out by Metgud et al, reported the diagnostic efficacy of saliva in evaluating levels of MDA and GSH in smoking patients with OSCC (90). Tobacco represents an exogenous source of ROS that subsequently leads to oxidative stress.…”
Section: Oral Pemphigus Vulgaris (Opv)mentioning
confidence: 99%
“…Some analytical methods have been developed to study salivary oxidative stress biomarkers (glutathione peroxidase, catalase, protein carbonyls, 8-hydroxy-2'-deoxyguanosine), but few of them determined lipid peroxidation compounds, such as malondialdehyde (MDA) [14][15][16], and prostanoids (e.g. 15-F 2t -IsoP) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Принимая во внимание вышеизложенное и несомненную патогенетическую роль свободнорадикальных процессов в канцерогенезе и прогрессии опухолей [10] В работе использовали ультрадисперсный порошок железа, полученный из крупнодисперсных порошков с помощью плазменной технологии, основанной на испарении сырья (крупнодисперсного порошка или прутка) в плазменном потоке с температурой 5000-6000 К и конденсации пара до ультрадисперсных частиц требуемого размера (дисперсность частиц 30-50 нм). Форма НЧ была близка к сферической.…”
Section: Introductionunclassified